Personification in Czech Vernacular Names of Flowers and Birds - Lavička, David (Bohemica Olomucensia, 2024)
The article focuses on personification in Czech vernacular names of flowers and birds. It explores different forms of personification used in vernacular names and compares the metaphors in each of the two domains in order to show how flowers and birds are per- ceived with regard to anthropocentrism.
Keywords: Personification; Vernacular Names; Names of Birds; Names of Flowers; Linguistic Image of the World